Effect of imeglimin on metabolic dysfunction-associated steatotic liver disease in individuals with type 2 diabetes - Naruyoshi Gyoutoku; Yukihiro Inoguchi; Junjiro Rikitake; Mutsuyuki Demiya; Mizuki Gobaru; Ayako Nagayama; Shimpei Iwata; Nao Hasuzawa; Hitomi Nakayama; Kenji Ashida; Masatoshi Nomura (PLoS ONE, 2025)
Objective Preclinical studies, including animal and in vitro experiments, have suggested that imeglimin, a novel antidiabetic drug, may have beneficial effects on metabolic dysfunction-associated steatotic liver disease (MASLD). However, its effect on MASLD in individuals with type 2 diabetes remains unclear. This study aimed to evaluate whether imeglimin has beneficial effects in individuals with type 2 diabetes and hepatic enzyme abnormalities. Methods This multicenter, retrospective, single-arm study included 49 individuals with type 2 diabetes who newly initiated imeglimin treatment and continued it for six months. Individuals with chronic liver diseases other than MASLD were excluded. Treatment efficacy for liver function was defined as an ALT reduction of ≥11 IU/L, corresponding to the upper interquartile range of ALT reduction. Logistic regression analysis was performed to identify predictors of this treatment efficacy. Results Body mass index (BMI) and hemoglobin A1c (HbA1c) levels significantly decreased after six months of imeglimin treatment. Additionally, both alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels significantly decreased (ALT: 21.0 IU/L [13.0–39.0] vs. 17.0 [12.5–28.0], p = 0.002; AST: 21.0 IU/L [17.0–30.0] vs. 18.0 [16.0–26.0], p = 0.010, respectively). Logistic regression analysis showed that baseline ALT and AST levels were significant predictors of treatment efficacy for liver function, after adjusting for HbA1c and BMI levels (OR 1.06, 95% CI 1.02–1.12, p = 0.006; OR 1.12, 95% CI 1.06–1.23, p = 0.002, respectively). Furthermore, the receiver operating characteristic (ROC) curve for baseline ALT as a predictor demonstrated excellent discriminatory performance (Area under the curve: 0.905, p = 0.004). A cutoff value of 25 IU/L yielded 100% sensitivity and 77.8% specificity. Conclusion This exploratory study suggests that imeglimin may have beneficial effects in individuals with type 2 diabetes and elevated ALT (≥25 IU/L), potentially associated with MASLD. Randomized controlled trials are needed to confirm these findings.